This radiant life - Neveu, Chantal, 1964- (Literature in translation series., 2020)
"In this stunning long poem, Chantal Neveu draws from the lexicons of science, art, revolution, and corporeal movement to forge intense and extended rhythms that invoke the elements and spaces making up our world. This is poetry capable of holding life and death, solidarity, and love. Renewal. Breathing. In its brevity and persistence, This Radiant Life is a material call for action: it asks us to let go, even just a little bit, of our individuality in favour of mutuality, to arrive separately yet in unison at a radiance in which all living beings can thrive."--